Analysis the Effect of Profitability, Current Ratio, and Ownership Structure on Firm Value - Dede Muhamad Mahrus; Khofifa Mezza Mariana; Sarah Ramadhini; Rawi Rawi (IJEBD (International Journal of Entrepreneurship and Business Development))
Purpose: This study aims to analyze the effect of profitability, current ratio and ownership structure on firm value and dividend policy as moderation, in manufacturing sector companies listed on the Indonesia Stock Exchange during the period 2020-2023.